2019
DOI: 10.1155/2019/6352609
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Fracture Characterizations of Rocks under Dynamic Tension Test with Image Processing

Abstract: To investigate the fracture characterizations of rocks under high strain rate tensile failure, a series of dynamic Brazilian tests was conducted using Split Hopkinson pressure bar (SHPB), and a high-speed digital camera at a frame rate of 50,000 frames per second (FPS) with a resolution of 272 × 512 pixels was adopted to capture the real-time images and visualize the failure processes. Using the extracted cracks and image processing technique, the relationship between loading condition (impact velocity), crack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 55 publications
(73 reference statements)
0
6
0
Order By: Relevance
“…Figure 1 shows the flowchart of the proposed algorithm: the original corrosion image is converted from RGB color space to the HSI color model, followed by the application of histogram equalization and dark detail enhancement method to the component "I." e enhanced image is obtained by combining the enhanced "I" component with the original "H" and "S" components [6] and subsequent conversion to the RGB color space. e whole process is implemented using Matlab.…”
Section: Related Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 shows the flowchart of the proposed algorithm: the original corrosion image is converted from RGB color space to the HSI color model, followed by the application of histogram equalization and dark detail enhancement method to the component "I." e enhanced image is obtained by combining the enhanced "I" component with the original "H" and "S" components [6] and subsequent conversion to the RGB color space. e whole process is implemented using Matlab.…”
Section: Related Theorymentioning
confidence: 99%
“…At present, image enhancement algorithms mainly include single-scale Retinex (SSR) and multiscale Retinex (MSR) enhancement methods, which are based on the color sense consistency model [5][6][7], direct enhancement method aiming at pixel grayscale [8,9], homomorphic filtering enhancement method [10,11], enhancement method of defogging with respect to the dark channel priori theory [12,13], image enhancement algorithm based on wavelet transform, and histogram equalization algorithm [14,15]. Each of the above methods has its own advantages and can be used in relevant application scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…The crack propagation can be divided into three modes. Ai et al 29 indicated that the impact velocity has an important in uence on the crack propagation process and dynamic mechanical properties. The crack fractal dimension increases with the increase of the crack propagation velocity.…”
Section: Introductionmentioning
confidence: 99%
“…Shen et al (2022) indicated that the loading rate has an effect on the energy release and the generation of new cracks. Ai et al (2019) indicated that the impact velocity has an important influence on the crack propagation process and dynamic mechanical properties. Song et al (2019) studied the evolution of prefabricated cracks in coal and rock samples under uniaxial compression.…”
Section: Introductionmentioning
confidence: 99%